Effects of shoulder geometry of tool on microstructure and mechanical properties of friction stir welded joints of AA1100 aluminum alloy (2017)
In this work were studied the effects of shoulder geometry of tool on microstructure evolution and mechanical properties of friction stir welded joints of AA1100 aluminum alloy using a milling machine. Three designs of shoulder geometry were evaluated with the aim to induce different distributions of thermal cycles in welding regions. Thermal cycles were measured using thermocouples and a data system acquisition. A microstructural characterization and crystallographic analysis of the welded regions were carried out using optical, scanning electron microscopy, and electron backscattering diffraction. The mechanical properties were measured by transverse tension, guided bend and hardness tests. The weldability behavior was established based on the experimental data. Results showed that the features shoulder tools produced an important effect on the thermal cycles, generating a plasticized wide region and biggest grain size in stir zone when compared with flat shoulder tool.